Synergistic Effect of Magnetic Composites on Zirconia Mineral for the Reduction of Eminent Pb (II) and Cd (II) from Synthetic Wastewater - Hema Avrilia; Agustiya Nuraini; Chairul Irawan; Iryanti Fatyasari Nata; Meilana Dharma Putra; Primata Mardina; Rinny Jelita; Muhammad Al Muttaqii (Sustainable Chemical Engineering, 2025)
Water contamination by heavy metals represents a critical global environmental challenge, necessitating the development of efficient and sustainable treatment solutions. The significant potential of Zirconia (ZrO2) as a high-quality adsorbent remains underdeveloped, particularly in Indonesia, for water treatment and purification applications. This is especially relevant given the growing environmental concern over heavy metal contamination in water supplies. This research aims to address this by developing zirconia-based magnetic particles for use as an efficient adsorbent. Zirconia-coated magnetic particles (Fe3O4@ZrO2) were synthesized via chemical co-precipitation. The adsorbent was then characterized using Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray spectroscopy (EDX), X-Ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR), which confirmed that modifying ZrO2 with Fe3O4 altered its structure, creating particles with a greater surface area ideal for adsorption. Subsequent adsorption tests for Pb (II) and Cd (II) demonstrated excellent removal capabilities, with maximum adsorption capacities of 189.21 mg/g and 85.22 mg/g, respectively. The combination of ZrO2 adsorption properties with the magnetic characteristics of Fe3O4 shows great promise for applications in water treatment and wastewater management, offering a potential method for reducing heavy metal pollutants.